Could laser‐assisted dissection of the pre‐epiglottic space affect functional outcome after ESL?. (27th October 2017) - Bertolin, Andy; Lionello, Marco; Russo, Simone; Rizzotto, Giuseppe; Lucioni, Marco
Abstract : Objectives: To evaluate the effect of preepiglottic space (PES) dissection in the endoscopic supraglottic laryngectomy (ESL). Study Design: A retrospective cohort study. Methods: We retrospectively compared 15 patients who underwent ESL with 15 patients matched for clinical stage who underwent open partial horizontal laryngectomy (OPHL). The functional outcomes were assessed in terms of hospital stay; need for nasal feeding tube (NFT) and tracheostomy, as well as duration of their use; postoperative complications; aspiration pneumonia rates; voice quality; and dysphagia. Results: Among the ESL cases, combined dissection of the epiglottis and PES (type III) had a negative impact on functional outcomes. ESL patients experienced shorter hospital stays, as well as shorter use of NFT and tracheostomy, than patients who had OPHL. Conclusion: Combined dissection of the epiglottis and PES (ESL type III) negatively affected functional outcome in patients undergoing ESL, a procedure generally related to significantly better functional outcomes than OPHL type I. Level of Evidence: 4. Laryngoscope, 128:1371–1378, 2018